CARDIOVASCULAR EFFECTS OF DUAL VACCINATION WITH PNEUMOCOCCAL PV23 AND INFLUENZA: A SYSTEMATIC REVIEW - Sotelo-Velasquez Yulied Angie; Rincón Augusto Cesar; Rojas Ruiz Tatiana Ingrid; Novoa-Alvarez Andrés Ricardo; Ramos Espinosa Gustavo; Méndez Toro Arnold (Sanamed)
The pneumococcal vaccine may reduce cardiovascular events. This systematic review examines the impact of PV23 and seasonal influenza vaccination on major cardiovascular outcomes compared to unvaccinated populations. We systematically reviewed clinical trials, cohort studies, and case-control studies published between 2000 and 2019 evaluating cardiovascular outcomes in adults vaccinated with PV23 and seasonal flu vaccines versus unvaccinated adults. Nineteen articles encompassing 617,411 patients were included. PV23 vaccination alone was not significantly associated with reduced acute myocardial infarction risk (RR 1.21 [95% CI: 1.18–1.23]). Dual vaccination showed a protective effect against stroke (RR 0.52 [95% CI: 0.45–0.61]) and significantly improved heart failure outcomes (RR 0.26 [95% CI: 0.22–0.31]). PV23 and dual vaccination also decreased episodes of acute heart failure decompensation and stroke development.